STUDI KINETIKA KRISTALISASI - Soni Sukendar, ; Triwikantoro, (Matematika dan Sains, 2009)
The crystallization kinetic of metallic glass Zr69.5Cu12Ni11Al7.5 was studied by using differential scanning calorimetry (DSC). The activation energy for such the crystallization of the amorphous phase was about (268 ± 5.7) kJ mole-1 calculated from Arrhenius plot. The crystallization process correspond to the normal Arrhenius plot with a constant linear slope. These results show that the mechanism and activation energy for the crystallization of Zr69.5Cu12Ni11Al7.5 alloy are not temperature-dependent. The order of crystallization (Avrami exponent) was calculated by using the JohnsonMehlAvrami (JMA) plot. The average value of the Avrami exponent was about (2,58 ± 0.29) at the range from 663K to 683 K. 69.5Cu12Ni11Al7.5 was studied by using differential scanning calorimetry (DSC). The activation energy for such the crystallization of the amorphous phase was about (268 ± 5.7) kJ mole-1 calculated from Arrhenius plot. The crystallization process correspond to the normal Arrhenius plot with a constant linear slope. These results show that the mechanism and activation energy for the crystallization of Zr69.5Cu12Ni11Al7.5 alloy are not temperature-dependent. The order of crystallization (Avrami exponent) was calculated by using the JohnsonMehlAvrami (JMA) plot. The average value of the Avrami exponent was about (2,58 ± 0.29) at the range from 663K to 683 K.